2021
DOI: 10.1002/jac5.1488
|View full text |Cite
|
Sign up to set email alerts
|

Impact analysis of virtual ambulatory transplant pharmacists during COVID‐19

Abstract: Introduction During the coronavirus disease 2019 (COVID‐19) pandemic, transplant centers were challenged to meet the demand for new telemedicine strategies. The ability of lung transplant providers (LTP) to conduct face‐to‐face clinic visits for high‐risk immunocompromised patients, such as lung transplant recipients (LTR), was limited. Through the implementation of comprehensive medication management visits, pharmacists were able to assist LTP in the transition to telemedicine. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Patients reported a similar quality of care with telephone medication reviews and found them to be convenient and effective. This study supports existing literature that pharmacists have a positive impact on clinical outcomes and maintain clinical services with telephone-based care, with evidence from individual studies and systematic reviews indicating this positive impact existing across clinical care disciplines and in both outpatient and inpatient settings [ 6 , 7 , 8 , 9 , 10 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 86%
“…Patients reported a similar quality of care with telephone medication reviews and found them to be convenient and effective. This study supports existing literature that pharmacists have a positive impact on clinical outcomes and maintain clinical services with telephone-based care, with evidence from individual studies and systematic reviews indicating this positive impact existing across clinical care disciplines and in both outpatient and inpatient settings [ 6 , 7 , 8 , 9 , 10 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 86%
“…After removing duplicates (n=795), and screening by the title and abstract (n=230) and full text (n=121), 43 articles were included in this review 20–62. Among the included studies were 25 observational studies (including 13 cross-sectional studies,36–39 43–48 54 59 60 5 case series,34 35 49–51 5 retrospective study,40 41 52 53 55 1 prospective study61 and 1 interview study42 and 18 descriptive studies 20–33 56–58 62. The general characteristics of the included studies are summarised in online supplemental table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the included studies are summarised in online supplemental table 1. The majority of the studies reported about the use of eHealth by hospital pharmacists,20 21 23 25 29–31 33–35 37–41 43 46–49 52–55 58 59 61 followed by community pharmacists 28 35 45 46 50 51 54 60 62. Patients with chronic diseases27 31 32 34 37 39 40 43 44 48 52 54 57 60–62 were the primary targets populations of PC-eHealth interventions, followed by patients with COVID-1926 34 42 46 49–51 58 and patients with cancer 27 31 37 40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the services included providing patient counseling and monitoring medication adherence. A study from a transplant clinic evaluated the services provided by ambulatory transplant pharmacists during the pandemic (Park et al, 2021). Within a seven-month period, 385 virtual clinic visits were conducted with lung transplant recipients with more than 890 interventions made, most of which were related to medications errors and involved patient education.…”
Section: Specialized Clinical Pharmacistsmentioning
confidence: 99%